Abyss - Hagberg, David (Hagberg, David. Kirk McGarvey adventures., 2011)
When an NOAA scientist has a breakthrough that could enable a sustainable energy source and prevent dangerous weather systems, former CIA director Kirk McGarvey begins a cat-and-mouse chase with a contract killer seeking to trigger a nuclear disaster.